SOCIAL TRANSFORMATION AND BIBLICAL INTERPRETATION: A COMPARATIVE STUDY - Jonker, Louis C. (Scriptura, 2001)
This article firstly summarizes the research results of the project "The influence of different contexts of social transformation on Biblical interpretation". If indicates and discusses the trends with regard to the interaction between social transformation and Biblical interpretation that became apparent from each of the different case studies that were done. Secondly, a comparative study is done within the interdisciplinary framework that was explored earlier in this project. The comparative study represents an attempt at generalising in order to contribute to our understanding of the intrecate relationship between social trnaformation and Biblical interpretation.